(untitled) (AmS-Varia, 2020)
The cairn field at Eikebakken, Øvre Øksnevad, Klepp municipality, Rogaland, Norway, was excavated over the course of 26 weeks in the summer of 2016. The site had undergone an initial survey in 2008, indicating a total of 79 cairns. However, when the site was uncovered a total of 103 stone built structures were identified, as well as three separate settlement areas and evidence of prehistoric farming. The initial project plan and budget were written with the idea of focusing on a smaller number of more thoroughly excavated (i.e. single-context) cairns. The increased number of structures made this plan untenable. As the excavation progressed it also became clear that the single-context method was not returning the amount of data required. The excavation thus went through several major shifts in strategy in response to, primarily, the archaeology and the need to develop a representative data set, but also time/budgetary constraints and available labor resources. The strategy ultimately settled upon involved a much more rapid excavation of a larger number of cairns with a focus on the use of environmental evidence from the cairns, particularly material suitable for radiocarbon dating, but also a range of other methodologies, as a means of understanding the development of the cairn field. This article will discuss both the methodologies and prioritizations involved in the excavation and will present some brief, initial results.